A global human health risk assessment for octamethylcyclotetrasiloxane (D4). (20th October 2017) - Gentry, Robinan; Franzen, Allison; Van Landingham, C.; Greene, Tracy; Plotzke, Kathy
Highlights: A global "harmonized" risk assessment for D4 was conducted to meet international requirements. This assessment included a Monte Carlo analysis to determine significant routes of exposure. A PBPK model was used to estimate internal dose metrics associated with the POD and exposures. A MOS was estimated to compare the estimates of intake with the POD. Using a MOS approach removes the subjective application of uncertainty factors. Abstract: Octamethylcyclotetrasiloxane (D4 ) is a low-molecular-weight volatile cyclic siloxane, primarily used as an intermediate in the production of some widely-used industrial and consumer silicone based polymers and may be present as a component in a variety of consumer products. A global "harmonized" risk assessment was conducted to meet requirements for substance-specific risk assessments conducted by regulatory agencies such as USEPA's Integrated Risk Information System (IRIS), Health Canada's Chemical Management Program (CMP) and various independent scientific committees of the European Commission (e.g. the Scientific Committee on Consumer Safety (SCCS), the Scientific Committee on Health and Environmental Risks (SCHER)), as well as to provide guidance for chemical safety assessments under REACH in Europe. This risk assessment incorporates global exposure information combined with a Monte Carlo analysis to determine the most significant routes of exposure. Utilization of a multi-species, multi-route physiologically based pharmacokinetic (PBPK) model was included to estimate internal dose metrics, benchmark modeling was used to determine a point of departure (POD), and a margin of safety (MOS) evaluation was used to compare the estimates of intake with the POD. Because of the specific pharmacokinetic behaviors of D4 including high lipophilicity, high volatility with low blood-to-air partition coefficients and an extensive metabolic clearance that regulates tissue dose after exposure, the use of a PBPK model was essential to provide a comparison of a dose metric that reflects these processes. The characterization of the potential for adverse effects after exposure to D4 using a MOS approach based on an internal dose metric removes the subjective application of varying uncertainty factors from various regulatory agencies and allows examination of the differences between internal dose metrics associated with exposure and those associated with adverse effects.